Porous membranes based on poly(ether imide)-graft-poly(vinyl acetate) as a scaffold for cell growth. (March 2018) - Liu, Bin; Kuang, Jiangying; Shao, Leishan; Che, Xinyuan; Wang, Fei; Wang, Yinghan
A series of poly(ether imide)-graft-poly(vinyl acetate) copolymers with different molecular weights were synthesized successfully and characterized using Fourier transform infrared spectroscopy, ultraviolet–visible spectroscopy, proton nuclear magnetic resonance, gel permeation chromatography, differential scanning calorimeter, thermogravimetric analysis, and X-ray photoelectron spectroscopy analyses. These copolymers were used to fabricate honeycomb-structured porous films using the breath figure templating technique. The surface topology and composition of the highly ordered pattern film were further characterized using a scanning electron microscopy. The results indicated that the poly(ether imide)-graft-poly(vinyl acetate) graft molecular weight ratio influenced the breath figure film surface topology. A model was proposed to elucidate the stabilization process of the poly(ether imide)-graft-poly(vinyl acetate)-aggregated architecture on the water droplet–based templates. In addition, cell viability has been investigated via 3-(4, 5-dimethylthiazol-2-yl)-2, 5-diphenyltetrazolium bromide test, and the cell morphology on the honeycomb-structured poly(ether imide)-graft-poly(vinyl acetate) porous film has been evaluated using a fluorescence microscope. This porous film is shown to be suitable as a matrix for cell growth.